Synthesis and photocatalytic activity of Fe doped CuO nanoparticles and its kinetics study - Farzana Haider; Haseeba; Kafeel Ahmad Khan; Gul Asim Ullah Nabi (PT Pustaka Intelektual Sutajaya, 2026)
Nanosized copper oxide and iron doped copper oxide were synthesized using green synthesis method. The samples were characterized using UV- visible spectrophotometer, FT-IR, TGA, EDX SEM and XRD. The particles were irregular yet agglomerated due to interactions between the molecules and the produced NPs. The rate of photocatalytic reaction is greatly affected by the catalyst identity. A maximum degradation of 94.56% for undoped CuO and 97.80% for Fe doped CuO nanoparticles was obtained at 0.03gm of catalyst. The pseudo ﬁrst order kinetic model best ﬁtted to the experimental data. The Arrhenius equation to the rate constant (kApp) was also applied to undoped CuO and Fe doped CuO. The synthesized nanoparticles were cost effective, easy to use and provide greater yield